Leaf extract of neem (Azadirachta indica Adr. Juss.) modulates morphological and biochemical characteristics in maize (Zea mays L.) under water deficit stress - Riaz Hussain; Iram Shehzadi; Muhammad Sadiq; Abrar Ahmad; Nudrat Aisha Akram; Pedro Garcia-Caparros (International Journal of Applied and Experimental Biology)
Foliar spray of neem (Azadirachta indica Adr. Juss.) leaf extract was exogenously applied at pre-flowering stage to examine the changes in growth and physio-biochemical characteristics of two maize cultivars (Sultan and Sadaf) under different water regimes (100%, 75% and 60% field capacity). Water deficit conditions significantly reduced shoot fresh weight (SFW), shoot dry weight (SDW), root fresh weight (RFW), root dry weight (RDW), shoot length, root length, chlorophyll b, total soluble proteins and free proline, but it significantly increased ascorbic acid (AsA) and total phenolics in both maize cultivars. Foliar-applied leaf neem extract significantly improved SFW, SDW, RFW, RDW, shoot length, chlorophyll b and ascorbic acid concentrations, but it significantly minimized hydrogen peroxide (H2O2) contents. Application of 1.0% neem extract was effective in improving chlorophyll b and AsA contents, whereas 2.0% neem extract was beneficial for total soluble proteins and MDA contents. Of both maize cultivars, cv. Sultan was found to be drought sensitive and cv. Sadaf as drought tolerant. Exogenous application of leaf neem extract was suggested to be effective in enhancing drought stress tolerance in maize by improving plant growth and oxidative defense system.